The Role of Education and Health Budget Functions in Achieving SDG 1 at the Regional Government Level in Indonesia - Jessy Christina Dewi Kadimun; Rahma Masdar; Andi Chairil Furqan; Masruddin Masruddin; Muhammad Ichsan (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to analyze the effect of education and health budget allocations on the achievement of SDG 1 (No Poverty) in local governments in Indonesia. This study uses a positivist paradigm with multiple linear regression method. The research population includes 542 provincial/district/city local governments during the period 2018–2021, resulting in a total of 2,168 observation units. Using purposive sampling, a sample of 2,132 observation units was obtained. The findings show that the education and health budgets play a role in efforts to achieve SDG 1. In addition, control variables, such as the age of the government, have no effect on SDG 1. This study encourages local governments to increase and ensure that education and health budgets are allocated evenly and effectively to support the achievement of SDG 1. This study has a number of limitations, including the use of data limited to a four-year period and an analysis focus that only covers one of the 17 global SDG goals, namely Sustainable Development Goal 1 (No Poverty). This study highlights the crucial role of local government function budgets in supporting the achievement of SDG 1.